(untitled) - Watson, Burton (New York,London, 1961)
Not much is known about the life of the Chinese historian Ssu-ma Ch'ien outside of the little information he gives us in the autobiography appearing at the eng of his life work, the Shih Chi, or Records of the historian. most scholars place his birth in 145 B.C. and agree that he died around 90 B. C. , so that his lifetime more or less parallels that of emperor Wu, the vigorous, strong-willed ruler who brought the han dynasty to its peak of power and at whose court Ssu-ma Ch'ien spent most of his life.
Keywords: China; History